“Por que você não confia no seu potencial? Para tudo, Gata!": análise do discurso de autoajuda para adolescentes - Carvalho, Cláuberson Correa (2017)
This research aims to analyze linguistic and enunciative features of self-help discourse for teenagers. We are based on studies of French School of Discourse Analysis, more precisely in the enunciative-discursive perspective developed by Maingueneau (2008b, 2008c, 2013). The idea is to examine how the linguistic maneuvers performed by the enunciator form the constitution of his ethos. For this, we use a conception of ethos (MAINGUENEAU, 2008a, 2008b) that "draws" the image projection of the enunciator from marks on the discursive surface, that is, in the enunciation. We chose as corpus three editions published by Capricho magazine between January and March 2015. Based on the criteria of regularity and productivity, we chose four categories of analysis: linguistic modality, conversational markers, metaenunciation, and Aphorizing Enunciation. The analysis indicates that the ethos of the subject of self-help discourse for teenagers demands, on the one hand, effects of spontaneity, in search of the trait of involvement and empathy with the enunciate; and, on the other, effects of authority, in the manifestation of certainty and obligation that characterize its domain.